Traumatic Dental Injuries: A seven-year evaluation of peadiatric cases seen in a tertiary hospital. Issue 1 (April 2021) - Popoola, B.O.; Ajayi, D.M.
Abstract: Background: Early presentation, prompt and adequate interventions of Traumatic Dental Injuries (TDIs) are necessary to prevent unwanted sequelae/complications. Objectives: To assess the pattern of TDIs among the affected children, identify the treatments received and the resultant complications/sequelae. Methods: This was a retrospective review of dental records of all paediatric patients from December 2011 to December 2018. TDIs were recorded according to the WHO classification (1995). Information on the treatment received, clinical and radiographic sequelae of trauma were also retrieved. Data were analyzed using IBM SPSS software Version 22. Result: A total of 776 teeth (208 primary, 568 permanent) were traumatized in 513 patients (314 males, 199 females, mean age = 8.86 ± 4.04 years). The peak age at occurrence of trauma was 8 years. The majority of patients complained of broken teeth (51.5%), sustained injury at home (47.6%), had trauma due to a fall (88.7%) and presented after one year of trauma (27.3%). Three quarters of motorcycle accidents occurred in 6–12 year–old children. More young age groups sustained injuries at home compared with older age group (p = 0.000). Avulsion (26.1%) and uncomplicated crown fracture (38.2%) were the commonest injuries to primary and permanent dentitions respectively. The most common sequelae of trauma were pulpal necrosis followed by internal root resorption. Tooth extraction (42.8%) and root canal treatment (37.0%) were the commonest treatments given in both dentitions respectively. Conclusion: The pattern of TDIs appeared not to have changed considerably but motorcycle accidents contributed to the aetiology and pulpal necrosis was a major complication due to late presentation.